How Brand Vibes, Stellar Service, and Prime Location Fuel WOM (Word of Mouth) and Drive Bookings in the Hotel Industry - Di-An Guevarra San Diego; Zazli Lily Wisker (AIBPM Publisher, 2024)
This study aims to examine the effects of brand image, perceived value, customer service, and hotel location on word of mouth (WOM) among hotel customers. Additionally, it posits that purchase intention mediates the relationship between the independent variables. Primary quantitative data were collected through an online survey using the SurveyMonkey platform, with established scales measuring the variables under study. A total of 110 participants responded to the survey. Data were analyzed using multiple regression and the Macro PROCESS Model 4. The findings demonstrate that brand image, perceived value, and services emerged as critical factors influencing WOM. However, location does not seem to affect WOM and purchase intention. This indicates that customers are more inclined to book a hotel room and recommend it to others when they perceive high value in the services offered, even though the location is unfavorable. Excellent customer service enhances the overall guest experience, leading to higher satisfaction and an increased likelihood of recommending the hotel to others.